Early Diagnosis of COVID-19 in January 2020 - Tarro, Giulio (British Journal of Healthcare and Medical Research, 2025)
With reference to two books signed by Tarro a few months after the outbreak of the pandemic, “Covid 19 – The virus of fear” (June 2020) and then “Covid 19 – The nightmare is over” (June 2022), they were prophetic because, to give just two examples, in the first one, in addition to underlining the macroscopic errors of our Italian government, which acted only with ‘Tachipirina and watchful waiting’ and denying access to treatments (such as hydroxychloroquine and invermectin even though they are present, and not very expensive, in all pharmacies) legalized only in December 2022 after an order of the Council of State, it has put the spotlight on those mechanisms of fear, panic, terror used by Western governments to chloroform and enslave citizens, forced into those nefarious lockdowns (and then vaccines). In the second book, he extensively illustrated the adverse effects caused by 'Covid products', especially those with mRMA (such as Pfizer and Moderna) which, completely experimental, not very effective and even more unsafe, have caused and are causing enormous problems, in particular affecting the cardiovascular system, with increases in pericarditis, myocarditis, strokes, thrombosis and heart attacks. But there is more. In the last book Tarro proposes the adoption of ad hoc GENETIC TESTS, to verify whether the organism of a certain individual can withstand the impact of the vaccine: fundamental tests (even if expensive, and our Italian State should take care of them) but never even taken into consideration by the governments that have succeeded one another, with the health of citizens rolling towards the abyss.